2018
DOI: 10.3390/nu10121924
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Type 2 Diabetes: Systematic Review

Abstract: Several studies have investigated the potential role of selenium (Se) in the development of type 2 diabetes (T2D) with disparate findings. We conducted a systematic review and meta-analysis to synthesize the evidence of any association between Se and T2D. PubMed, Embase, and Scopus were searched following the Preferred Reporting Items for Systematic Reviews and Meta-analysis Approach (PRISMA). Sixteen studies from 15 papers met inclusion criteria defined for this review. Of the 13 observational studies include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 34 publications
1
70
1
3
Order By: Relevance
“…As a chronic hyperglycaemia can cause a substantial increase of reactive oxygen species (ROS) and oxidative stress, leading to diabetes‐related complications and a decreased Se level , it was hypothesised that, in patients diagnosed with T2DM, Se supplementation may be beneficial. However, a number of studies indicate that it may act adversely on glucose homeostasis and insulin sensitivity and even increase the risk of T2DM . This can be partially explained by the impact of Se on selenoproteins and insulin signalling .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a chronic hyperglycaemia can cause a substantial increase of reactive oxygen species (ROS) and oxidative stress, leading to diabetes‐related complications and a decreased Se level , it was hypothesised that, in patients diagnosed with T2DM, Se supplementation may be beneficial. However, a number of studies indicate that it may act adversely on glucose homeostasis and insulin sensitivity and even increase the risk of T2DM . This can be partially explained by the impact of Se on selenoproteins and insulin signalling .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the potential benefits of Se need to be balanced with possible harms. Recently, in 2018, two systematic reviews of randomised controlled trials ( RCT s) showed equivocally the effect of selenium on T2DM development .…”
Section: Introductionmentioning
confidence: 99%
“…However, RCTs of selenium did not indicate a higher risk of T2D in individuals receiving selenium as compared with placebo group. In this study, the associations between selenium and risk of T2D were observed in the observational studies which were not repeated in the RCT studies [39].…”
Section: Discussionmentioning
confidence: 79%
“…Dabei hatten hohe Selen-und Kupferwerte einen höheren HbA 1c -Spiegel zur Folge. Ursächlich dafür könnte unter anderem eine Störung der Insulinsignalkaskade durch insulinähnliche Wirkungen von Selenoproteinen sein [9] [11].…”
Section: Selen Und Kupferunclassified
“…Bezüglich der Entstehung eines Typ-2-Diabetes nach Supplementierung gibt es bislang keinen Nachweis [11].…”
Section: Vorsichtunclassified